Headache with Isolated Sixth Cranial Nerve Palsy in an Overweight Woman: A Case of Idiopathic Intracranial Hypertension - Goe Xian Jeff; Sharifah Najwa Syed Mohamad; Siti Noorfaezah Abdul Kadir; Syed Hussein Barakbah (USIM PRESS, 2024)
Malaysian Journal of Science, Health & Technology (MJoSHT) Volume 10 Issue 1 Page (69-72)